Analysis of the rights of disabilities persons from critical theory - Molina Díaz, Karla (2016)
This research focuses on the analysis of the human rights from non-traditional theoretical renowned, critical theory, applied to the case of the population with disability like subject of formalized rights that demand the satisfaction worthy of the access to the most basic things. This theory is characterized for being a discursive rationality of liberating character of the subject opposite to the oppres-sion, marginality and discrimination of the current system, in contrast with the usual collision of the human dignity and equality of the individuals before the Law, who try to provide with more rights the vulnerable populations in spite of the already existing ones, without questioning the possible contradictions be-tween the speeches and its concepts with the reality conflictual. The work be organized in three chapters: the complexity of the concept of human rights; the absolutism of the law as a unique alternative and why other Convention rights?